Novel CFD-based numerical schemes for conduction dominant encapsulated phase change materials (EPCM) with temperature hysteresis for thermal energy storage applications. (1st August 2017) - Kumarasamy, Karthikeyan; An, Jinliang; Yang, Jinglei; Yang, En-Hua
Abstract: Encapsulated phase change materials (EPCM) are the most common way to integrate with thermal systems for energy storage applications. Encapsulation greatly alters the thermal response of phase change materials (PCM) in terms of phase change temperatures and thermal hysteresis. Existing numerical schemes; however, can only simulate bulk PCM behavior and ignore the influence of encapsulation on the thermal response of EPCM. In this study, novel computational fluid dynamics (CFD)-based conduction dominant numerical schemes are developed for the first time to model the thermal response of EPCM and validated with the experimental DSC curve of the in-house fabricated EPCM capsules. The proposed heat source/sink scheme successfully predicts the heat-temperature responses and liquid volume fraction of EPCM with thermal hysteresis. It is recommended that the CFD-based conduction dominant heat source/sink scheme developed for EPCM in current study should be incorporated into energy simulation softwares for accurate performance predication when EPCM capsules are expected to be used in thermal energy storage systems and applications. Highlights: Novel CFD-based numerical schemes to model conduction dominant encapsulated phase change materials (EPCM). Heat source/sink scheme to predict thermal response of EPCM with thermal hysteresis. Validation with experimental DSC results. Computational efficiency comparison of schemes.